Efek Antiinflamasi Krim Ekstrak Etanol Daun Kirinyuh (Chromolaena odorata (L) R.M. King & H. Rob ) Secara Topikal Dan Penentuan Jumlah Sel Leukosit Pada Mencit Putih Jantan - Ifora Ifora; Helmi Arifin; Rella Silvia (STIFARM Padang, 2017)
The research about the anti-inflammatory effect of ethanol extract of kirinyuh (Chromolaena odorata (L) R.M. King & H. Rob )that gave topically with granuloma pouch method. Inflammation was induced by carrageen 2 % in thesesame oil gave in subcutaneous. Extract administered topically in cream which was given on graded concentrate: 2,5 %; 5 % and 10 % for 4 days. Diameter of inflammation, volume of edema, and amount of leukocytes cell in the mice white male were being the parameter of this research. The parameter which was obtained at the end of the research was showed that the ethanol extract of kirinyuh(Chromolaena odorata (L) R.M. King & H. Rob ) in graded concentrate 2,5 %; 5 % and 10 % can suppress the increase of parameter. They were significant difference between increasing doses of ethanol extract of kirinyuh(Chromolaena odorata (L) R.M. King & H. Rob ) with graded dose to diameter of inflammation, volume of edema, and amount of leucocytes cell in the blood significantly (p<0.05).